Agency via Awareness: A Unifying Meta-Process in Psychotherapy - Gorlin, Eugenia I.; Békés, Vera (Frontiers in Psychology, 2021)
To address the need for conceptual and clinical consensus within the field, psychotherapy research has increasingly focused on identifying common principles of change. While the field contends that this approach is atheoretical, we posit that principles of change cannot be fully understood or applied without the context of some theoretical framework. This article develops such a framework by identifying and explicating two theoretical assumptions that are implicitly shared by multiple therapeutic approaches: 1) that increasing agency is a fundamental aim of psychotherapy, and 2) that therapists enhance clients’ agency by increasing their awareness. Building on the largely disparate empirical literatures demonstrating the importance of client agency and awareness to successful therapeutic outcomes, we provide a theoretical account of the highly iterative and synergistic meta-process by which these two factors jointly produce change. Explicit identification and empirical investigation of this Agency via Awareness psychotherapy meta-process, we argue, could facilitate scientific and clinical progress within the field. The hypothesized meta-process is discussed in relation to existing integrative models of therapeutic change, and its manifestations in the theory and practice of major therapeutic orientations are reviewed and illustrated. We discuss how this framework can facilitate psychotherapy research by providing a common language and conceptual foundation for wide-ranging therapeutic approaches, constructs, and findings. Finally, by raising clinicians’ awareness of the implicit assumptions underlying their therapeutic work, we suggest that the Agency via Awareness framework can increase their agency over when and how they apply these assumptions in therapy to maximize client improvement.